Satellite-Derived PM2.5 Composition and Its Differential Effect on Children’s Lung Function - Khang Chau (Remote Sensing, 2020)
Studies of the association between air pollution and children’s health typically rely on fixed-site monitors to determine exposures, which have spatial and temporal limitations. Satellite observations of aerosols provide the coverage that fixed-site monitors lack, enabling more refined exposure assessments. Using aerosol optical depth (AOD) data from the Multiangle Imaging SpectroRadiometer (MISR) instrument, we predicted fine particulate matter, PM <semantics> 2.5 </semantics> , and PM <semantics> 2.5 </semantics> speciation concentrations and linked them to the residential locations of 1206 children enrolled in the Southern California Children’s Health Study. We fitted mixed-effects models to examine the relationship between the MISR-derived exposure estimates and lung function, measured as forced expiratory volume in 1 second (FEV <semantics> 1 </semantics> ) and forced vital capacity (FVC), adjusting for study community and biological factors. Gradient Boosting and Support Vector Machines showed excellent predictive performance for PM <semantics> 2.5 </semantics> (test <semantics> R 2 </semantics> <semantics> = 0.68 </semantics> ) and its chemical components (test <semantics> R 2 </semantics> <semantics> = </semantics> −0.71). In single-pollutant models, FEV <semantics> 1 </semantics> decreased by 131 mL (95% CI: <semantics> − 232 , − 35 </semantics> ) per 10.7-µg/m <semantics> 3 </semantics> increase in PM <semantics> 2.5 </semantics> , by 158 mL (95% CI: <semantics> − 273 , − 43 </semantics> ) per 1.2-µg/m <semantics> 3 </semantics> in sulfates (SO <semantics> <msubsup> 4 2 − </msubsup> </semantics> ), and by 177 mL (95% CI: <semantics> − 306 , − 56 </semantics> ) per 1.6-µg/m <semantics> 3 </semantics> increase in dust; FVC decreased by 175 mL (95% CI: <semantics> − 310 , − 29 </semantics> ) per 1.2-µg/m <semantics> 3 </semantics> increase in SO <semantics> <msubsup> 4 2 − </msubsup> </semantics> and by 212 mL (95% CI: <semantics> − 391 , − 28 </semantics> ) per 2.5-µg/m <semantics> 3 </semantics> increase in nitrates (NO <semantics> <msubsup> 3 − </msubsup> </semantics> ). These results demonstrate that satellite observations can strengthen epidemiological studies investigating air pollution health effects by providing spatially and temporally resolved exposure estimates.